2006
DOI: 10.1007/s00586-006-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CAOS as a training model in spinal surgery: a randomised study

Abstract: The objectives of this study were (1) to quantify the benefit of computer assisted orthopaedic surgery (CAOS) pedicle screw insertion in a porcine cadaver model evaluated by dissection and computed tomography (CT); (2) to compare the effect on performance of four surgeons with no experience of CAOS, and varying experience of pedicle screw insertion; (3) to see if CT with extended windows was an acceptable method to evaluate the position of the pedicle screws in the porcine cadaver model, compared to dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Therefore, it could be argued that it would not be advisable to learn procedures which employ all these technological apparatus which would probably never be useful in real situations. [29] A critical review on the topic has recognized that computer-assisted operations (CAOS) involve additional surgical steps which take both time and manpower: Operations usually take longer; some products require additional imaging; all systems need to have infrared beacons anchored to bone and which produce significant further morbidity and risks, besides being very expensive (for some center almost prohibitive), has almost the same size as an image intensifier, taking up space in the operating suite and requiring specialized nursing support; and finally, the software contracts associated with each system, may be exorbitant. [30] Conclusions…”
Section: Assisted Technologiesmentioning
confidence: 97%
“…Therefore, it could be argued that it would not be advisable to learn procedures which employ all these technological apparatus which would probably never be useful in real situations. [29] A critical review on the topic has recognized that computer-assisted operations (CAOS) involve additional surgical steps which take both time and manpower: Operations usually take longer; some products require additional imaging; all systems need to have infrared beacons anchored to bone and which produce significant further morbidity and risks, besides being very expensive (for some center almost prohibitive), has almost the same size as an image intensifier, taking up space in the operating suite and requiring specialized nursing support; and finally, the software contracts associated with each system, may be exorbitant. [30] Conclusions…”
Section: Assisted Technologiesmentioning
confidence: 97%
“…[5][6][7][8] Simulation offers an opportunity for surgical trainees to gain experience carrying out difficult procedures with complex anatomy in a safe environment.…”
Section: Discussionmentioning
confidence: 99%
“…3 The potential of 3-dimensional software simulation in numerous areas of surgical training is well recognized. [5][6][7][8] The simulator is playing an increasingly important role in surgical training. Surgical trainees new to this operative technique can learn to appreciate the complex 3-dimensional anatomy of the spine, and the implications of small errors in insertion point placement, screw choice, angulation, and depth of insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This is only possible as the instrument applied is equipped with LEDs or reflector elements that are captured by a system of cameras which are connected to the computer that processes the images. 6,[11][12][13][14][15] Cadaveric [16][17][18][19][20][21][22][23] and clinical 8,[24][25][26][27][28][29] studies have demonstrated that neuronavigation in the vertebral column is a safe and accurate method that is more effective than conventional methods for implanting pedicle screws. In a clinical study comparing the precision of the positioning of pedicle screws in the thoracic and lumbosacral spine between the two methods, the authors found an error in the positioning of screws of 13.4% in the conventional surgery group and only 4.6% in the group that used neuronavigation.…”
Section: Introductionmentioning
confidence: 99%